In-Vitro Activity of Nano Fluconazole and Conventional Flucon-azole against Clinically Important Dermatophytes - Najmossadat MUSAVI BAFRUI; Seyed Jamal HASHEMI HAZAVEH; Mansour BAYAT (Tehran University of Medical Sciences, 2020)
Abstract Background: Dermatophytosis is one of the most common fungal infections in humans. Antifungals such as fluconazole are effectively used for treating dermatophytosis; however, drug resistance was observed in many cases. Therefore, a newer treatment strategy is essential. Methods: This study (Conducted in the Laboratory of the School of Public Health, Tehran University of Medical Sciences, Tehran, Iran in 2018) evaluated the antifungal susceptibility of nano fluconazole compared to conventional fluconazole on dermatophyte isolates using CLSI M38-A2guidelines. Dermatophyte species isolated from clinical cases of dermatophytosis were identified using PCR sequencing techniques. Zeta potential and size of the nano particles containing fluconazole were measured; scanning electron microscope (SEM) was used to determine nano particle structure. Results: The size of liposomal fluconazole obtained was 88.9  12.14 nm with -20.12  3.8 mV for zeta potential. The encapsulation rate for fluconazole was 75.1  4.2%. MIC50 for the three tested species was 32, 16, and 8 μg/ml for Trichophyton interdigitale, T. rubrum, and Epidermophyton floccosum isolates, respectively. The corresponding values for nano fluconazole were 8 μg/ml for the three tested species. Conclusion: MIC value for nano-fluconazole was lower than conventional fluconazole in all dermatophytes species tested; therefore, nano-fluconazole could inhibit the growth of dermatophytes better than fluconazole at a lower concentration of the drug.